Performance evaluation of palm oil clinker as cement and sand replacement materials in foamed concrete - Salari, Farhang; Johnson Alengaram, U.; Alnahhal, Ahmed Mahmoud; Ibrahim, Zainah; Srinivas M, Karthick; Ibrahim, Muhammad S. I.; N, Anand (Journal of Civil Engineering and Management, 2023)
Cellular lightweight concrete (CLC), also known as foamed concrete, has been extensively used in construction for decades. Foamed concrete’s properties include low density, excellent thermal conductivity, great workability, and selfcompaction; these features enable foamed concrete to be utilized in various contexts. However, the excessive use of conventional materials in concrete production harms the environment. Therefore, using agro-waste as a material to construct ecologically sustainable structures has numerous practical and financial benefits. Palm oil clinker (POC) is a waste product resulting from solid waste combustion during palm oil extraction. This research focused on the properties of foamed concrete with POC at 0%, 25%, 50%, 75%, and 100% as the fine aggregate replacement to develop lightweight foamed concrete (LFC) with a density of 1300 kg/m3. Besides, the potential of POC powder (POCP) and thermally activated POCP (TPOCP) at 0%, 10%, 20%, and 30% as cement replacements was examined. The development of compressive strength during a 90-day curing period was investigated. In addition, tensile and flexural strengths were assessed and reported, and the elastic modulus of the LFC was discussed. The transport properties of water absorption, porosity, and sorptivity were also investigated. The durability of concrete derivatives can exhibit the product’s resistance to chemical attacks and environmental conditions. After 75 days of immersion in hydrochloric acid and magnesium sulfate, the chemical resistivity of the produced LFC was determined by measuring the loss in weight and compressive strength. In addition, the effects of elevated temperatures on the LFC were determined by analyzing the mass loss and compressive strength degradation of specimens exposed to temperatures ranging from 200 to 800 °C. The test results demonstrated that the complete replacement of sand with POC enhanced the compressive strength of LFC by more than 50%. Similarly, POC-based LFC had higher flexural and tensile strengths than normal LFC. Besides, substituting 20% of cement with TPOCP could improve the strength of LFC by 23% during the initial curing days. Utilizing the optimal proportions of POC and POCP could enhance the residual strengths of LFC. Therefore, POC has the potential to be utilized as a fine aggregate and cementitious material to produce sustainable concrete.